(3GdYdGbGJ GdYGeI aj GdJWHjbs - (3YHO GdQRGb eMeO(B, (3GdOjdejs ((3YeGf(B:s (3OGQ LQjQ ddfTQ hGdJhRjY(B,s, 2005)
(3JLO aj gPG GdcJGH (B: (3GdYdGbGJ GdYGeI hJWhQgG GdJGQjNj aj GdYGde , JCSjS GdYdGbGJ GdYGeI , GdeHGOF GdCSGSjI ddYdGbGJ GdYGeI , GdJfXje GdOGNdj ddYdGbGJ GdYGeI , COhGQ egeI ddYdGbGJ GdYGeI , GdJNWjW aj GdYdGbGJ GdYGeI ,GdYdGbGJ GdYGeI aj GdEOGQI GdMchejI , GdYdGbGJ GdYGeI aj HYV GdeDSSGJs
Keywords: (3GdYdGbGJ GdYGeIs